Navigating Clinician-Researchers’ Duties in Decentralized Clinical Trials - Patrinos, Dimitri; Zawati, Ma’n (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2026)
Decentralized clinical trials (DCTs) are clinical trials in which some or all trial-related procedures take place outside traditional clinical trial sites. Digital technologies have played an important role in enabling the remote conduct of clinical trials, and it is anticipated that many clinical trials will adopt full or hybrid decentralized models. While DCTs present many benefits and opportunities to streamline and improve the conduct of clinical trials, there are also several challenges in their implementation. These include privacy and confidentiality risks, challenges in trial oversight and monitoring, digital literacy, and participant compliance. To address these challenges, it is essential to clarify the ethico-legal duties of clinician-researchers, who are responsible for the overall conduct of clinical trials. This article analyzes these duties and identifies key factors needed to support the adoption of DCTs while safeguarding participants’ health, safety, and well-being.